Melanchthon's Role in the Reformation of the University of Tübingen - Harrison, Richard Leigh (Church history, 1978)
When Ulrich, Duke of Württemberg, regained his ducal throne in May of 1534, he immediately took steps to institute the Reformation in Württmberg. Probably because of his own divided loyalties, he asked both Lutherans and Swiss-Reformed Protestants to come to Württemberg. From the outset, however, their mutual opposition, combined with determined Roman Catholic resistance in some areas, led to difficulties beyond Ulrich's expectations. The ducal commissioners for the Reformation in the southern half of Württemberg was Ambrosius Blarer, the reformer of Constance and a firm ally of both Martin Bucer and Zurich. Part of his responsibility was the University of Tübingen, a center of particularly strong Roman Catholic opposition to the Reformation. Blarer appealed to Duke Ulrich for assistance, asking for the Basel Greek scholar Simon Grynaeus, another Swiss partisan. Ulrich, however, took far more dramatic steps to reform the University of Tübingen. Under instructions from Ulrich, Chancellor Knoder and Erhard Schnepff, Blarer's counterpart in northern Württemberg, wrote to Philip Melanchthon, requesting that he return to his homeland to teach in the University of Tübingen, his alma mater.